Networked micro-grid topologies for transactive energy management system: An overview and future perspectives - Stephen Oko Gyan Torto; Rupendra Kumar Pachauri; Jai Govind Singh; Baseem Khan; Ahmed Ali (Scientific African)
Networked micro-grid topologies are important for several reasons. First, they make it possible to connect decentralized energy sources like solar PV installations, micro- and mini-scale wind turbines, etc., to the main power grid. This has the potential to lessen the grid's reliance on fossil fuels while also improving its efficiency and dependability. Second, micro-grids can provide a level of resilience to the grid, as they can operate independently during power outages or other disruptions. This can be particularly important in disaster-prone areas or for critical infrastructure such as hospitals or emergency services. The problems that arise from managing the current or conventional power grid can be alleviated, in part, with the use of TEM. This study will introduce TEM and discuss its usefulness in several contexts, including the energy market, grid design, and functioning. Also, discuss the various existing power generation players involved in the development of market structure frameworks. This study concludes and highlights the significant role and effectiveness of energy system schemes for power exchange networked management systems. In addition, to the future perspective and power demand, attention to the de-centralized micro-grid model makes a comparison to the centralized and partially de-centralized topologies based on the Pros and Cons of the present study. In summary, networked micro-grid topologies play a crucial role in improving grid efficiency and dependability, ensuring continued service during blackouts, and fostering the widespread use of renewable energy sources.